2018
DOI: 10.1002/jcp.27735
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from acute myeloid leukemia cells promote chemoresistance by enhancing glycolysis‐mediated vascular remodeling

Abstract: Acute myeloid leukemia (AML) is the most common type of leukemia in adults. AML cells secrete angiogenic factors to remodel vasculature and acquire chemoresistance; however, antiangiogenic drugs are often ineffective in AML treatment. Cancer cell‐derived exosomes can induce angiogenesis, but their role in vascular remodeling during AML is unclear. Here, we found that exosomes secreted by AML cells promoted proliferation and migration and tube‐forming activity of human umbilical vein endothelial cells (HUVECs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…Recently, research shows that exosomes secreted by cancer cells can remodel the metabolism of ECs. Wang et al 72 found that exosomes derived from acute myeloid leukemia (AML) cells, containing VEGF/VEGFR, could promote the glycolysis in ECs. Although recent studies have discovered the potential role of exosomes secreted by cancer cells on regulating the metabolism of ECs, few studies have focused on the feedback effects of ECs-derived exosomes on cancer cells in the tumor field.…”
Section: Exosome-mediated Metabolic Reprogramming In the Tmementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, research shows that exosomes secreted by cancer cells can remodel the metabolism of ECs. Wang et al 72 found that exosomes derived from acute myeloid leukemia (AML) cells, containing VEGF/VEGFR, could promote the glycolysis in ECs. Although recent studies have discovered the potential role of exosomes secreted by cancer cells on regulating the metabolism of ECs, few studies have focused on the feedback effects of ECs-derived exosomes on cancer cells in the tumor field.…”
Section: Exosome-mediated Metabolic Reprogramming In the Tmementioning
confidence: 99%
“… 104 , 105 Recently, Huang et al found that exosomes derived from AML cells could regulate vascular reprogramming in AML. 72 VEGF-containing exosomes were transferred into the targeted ECs, and induced the upregulation of glycolytic capacity and angiogenesis activity in ECs through activating VEGF signaling. 72 Virus-encoded microRNAs packed in exosomes from Kaposi’s sarcoma-associated herpesvirus (KSHV) infected cell were incorporated by the neighboring cells, resulting in metabolism shifted toward the glycolysis and reduced mitochondrial biogenesis in surrounding non-infected cells.…”
Section: Exosome-mediated Metabolic Reprogramming In Cancer Progressimentioning
confidence: 99%
See 2 more Smart Citations
“…AML (acute myeloid leukemia)-derived exosomes foster the chemoresistance of AML cells to cytarabine, as they secrete VEGF/VEGFR factors to promote glycolysis in human umbilical vein endothelial cells (HUVECs) [ 174 ]. Several reports described the EV-mediated resistance transfer from resistant AMLs to sensitive AMLs by miRNAs for modulating expression of apoptotic proteins [ 175 , 176 , 177 ].…”
Section: Exosomes and Radio- And Chemo-resistancementioning
confidence: 99%